2014
DOI: 10.2478/agp-2014-0014
|View full text |Cite
|
Sign up to set email alerts
|

Stromatoporoid Beds and Flat-Pebble Conglomerates Interpreted as Tsunami Deposits in the Upper Silurian of Podolia, Ukraine

Abstract: ABSTRACT:Łuczyński, P., Skompski, S. and Kozłowski, W. 2014. Stromatoporoid beds and flat-pebble conglomerates interpreted as tsunami deposits in the Upper Silurian of Podolia, Ukraine. Acta Geologica Polonica, 64 (3), 261-280. Warszawa.Tsunami deposits are currently a subject of intensive studies. Tsunamis must have occurred in the geological past in the same frequency as nowadays, yet their identified depositional record is surprisingly scarce. Here we describe a hitherto unrecognized example of probable pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 71 publications
0
12
0
Order By: Relevance
“…The bioclast concentration with an erosional base and normal graded-bedding shallowing-upward cycles, presence of Pebbles with size ranges between 6 to 100 mm (Fig. 12b), cross-lamination and few micro-HCS and randomly oriented was properly occurred in channels created by a storm (Adabi and Rao 1991;Łuczyński et al 2014). In Fig.…”
Section: Sequence Stratigraphymentioning
confidence: 96%
“…The bioclast concentration with an erosional base and normal graded-bedding shallowing-upward cycles, presence of Pebbles with size ranges between 6 to 100 mm (Fig. 12b), cross-lamination and few micro-HCS and randomly oriented was properly occurred in channels created by a storm (Adabi and Rao 1991;Łuczyński et al 2014). In Fig.…”
Section: Sequence Stratigraphymentioning
confidence: 96%
“…In the Podolian succession, parabiostromal accumulations interbedded within shallow-water lagoonal sediments have been interpreted as resulting from high-energy sedimentary events driving onshore redeposition of skeletal material [ 30 , 35 ]. Some of these biostromes composed of broken and redeposited specimens were described as tsunami deposits [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of a palaeotsunami record in the shallow-water Upper Devonian deposits of the Holy Cross Mountains has been previously suggested by Kaźmierczak and Goldring [ 37 ], who based this premise on their interpretation of flat pebble conglomerates deposited in a subtidal setting. This is especially intriguing given that flat pebble conglomerates of an alleged tsunami genesis also accompany the stromatoporoid parabiostromes of Podolia [ 36 ]. That being said, the high energy facies (mainly developed as variously coarse-grained deposits ranging from calcarenites to carbonate breccias, commonly with abundant bioclastic material) that are interbedded upon, and fringe the flanks of, the Devonian shallow-water carbonate platform deposits of the Holy Cross Mountains, have usually been interpreted as associated with storms [ 38 – 40 ] or gravitational phenomena [ 41 , 42 ], rather than with tsunamis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our earlier studies (Skompski et al 2008;Łuczyński et al 2009, 2014 have revealed that part of these beds, particularly those in the higher part of the Silurian succession, are in fact represented by sediments composed of material redeposited shoreward and derived from open marine regions. One can assume that some of the stromatoporoid biostromes on Gotland are of a similar origin (compare, Kershaw 1990).…”
Section: Introductionmentioning
confidence: 99%